Fundamental Insights into the Covalent Silane Functionalization of NiFe Layered Double Hydroxides - Carrasco, Jose A.; Seijas-Da Silva, Alvaro; Oestreicher, Víctor; Romero, Jorge; Márkus, Bence G.; Simon, Ferenc; Vieira, Bruno J.C.; Waerenborgh, João C.; Abellán, Gonzalo; Coronado, Eugenio (Chemistry - A European Journal, 2020)
Layered double hydroxides (LDHs) are a class of 2D anionic materials exhibiting wide chemical versatility and promising applications in different fields, ranging from catalysis to energy storage and conversion. However, the covalent chemistry of this kind of 2D materials is still barely explored. Herein, the covalent functionalization with silanes of a magnetic NiFe-LDH is reported. The synthetic route consists of a topochemical approach followed by anion exchange reaction with surfactant molecules prior to covalent functionalization with the (3-aminopropyl)triethoxysilane (APTES) molecules. The functionalized NiFe-APTES was fully characterized by X-ray diffraction, infrared spectroscopy, electron microscopy, thermogravimetric analysis coupled with mass spectrometry and 29Si solid-state nuclear magnetic resonance, among others. The effect on the electronic properties of the functionalized LDH was investigated by a magnetic study in combination with Mössbauer spectroscopy. Moreover, the reversibility of the silane-functionalization at basic pH was demonstrated, and the quality of the resulting LDH was proven by studying the electrochemical performance in the oxygen evolution reaction in basic media. Furthermore, the anion exchange capability for the NiFe-APTES was tested employing CrVI, resulting in an increase of 200 % of the anion retention. This report allows for a new degree of tunability of LDHs, opening the door to the synthesis of new hybrid architectures and materials.
CRIS-Team Scopus Importer:2020-04-17
Keywords: 2D materials; covalent functionalization; electrocatalysis; layered compounds; oxygen evolution reaction